2021
DOI: 10.17520/biods.2021014
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between tree diversity and biomass/productivity and their influence factors in a lower subtropical evergreen broad-leaved forest

Abstract: www.biodiversity-science.net 研究报告 indirectly. Therefore, it is a critical issue of ecology. The aim of this study is to quantitatively explore the relationship between tree diversity and biomass or productivity of subtropical natural forest ecosystems in late successional stages. Methods: Based on long-term community surveys of topographies and soil nutrients from permanent forest ecosystems in the subtropical evergreen broad-leaved forest, we analyzed the relationship between tree diversity and productivity/b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
3
3
0
Order By: Relevance
“…In this study, it was found that the community structure was complex in the environment with high content of soil phosphorus and soil available potassium in karst primeval forest. While the environment with high soil organic carbon and soil nitrogen content reduced community structure, which was similar to the results of Zhu Jie et al's study [50]. The possible causes: soil nitrogen deposition affects the changes of species diversity and structural diversity, and the more nitrogen in soil, the lower the community species diversity and structural diversity, and the lower the biodiversity will affect the growth of forest productivity.…”
Section: The Relative Influences Of Biotic and Abiotic Factors On Com...supporting
confidence: 87%
See 2 more Smart Citations
“…In this study, it was found that the community structure was complex in the environment with high content of soil phosphorus and soil available potassium in karst primeval forest. While the environment with high soil organic carbon and soil nitrogen content reduced community structure, which was similar to the results of Zhu Jie et al's study [50]. The possible causes: soil nitrogen deposition affects the changes of species diversity and structural diversity, and the more nitrogen in soil, the lower the community species diversity and structural diversity, and the lower the biodiversity will affect the growth of forest productivity.…”
Section: The Relative Influences Of Biotic and Abiotic Factors On Com...supporting
confidence: 87%
“…Species in natural communities have evolved over a long period of time, forming a specific community structure of interdependence and interaction between species and the environment. The results of showed that topographic factors had no significant effect on biomass and productivity, which was consistent with the results of Zhu Jie et al's study on evergreen broad-leaved forests in the subtropical region [50], and different from the results of Wu Chuping' s study on secondary forest in Dinghai, Zhejiang [15], this indicates that the structure of the community is influenced by region and forest type. Elevation was positively correlated with species diversity, while slope was negatively correlated with species diversity.…”
Section: The Relative Influences Of Biotic and Abiotic Factors On Com...supporting
confidence: 83%
See 1 more Smart Citation
“…In a grassland ecosystem, Adler et al ( 2011 ) found that species diversity was not a good predictor of community productivity at different sampling scales. A possible explanation is that the available resources not only affect the maximum biomass that can be achieved by species in the area but also cause biomass to stop increasing (Zhu et al, 2021 ). On the other hand, scale can also lead to resource competition among species, thereby affecting the number of species.…”
Section: Discussionmentioning
confidence: 99%
“…Stands with high species diversity often have more complex stand structures and edge effects, and such stands can better utilize sunlight and soil fertility, thereby changing the microclimate in the forest and improving the growth environment in forest areas (Zhu et al, 2021 ). Furthermore, this can increase the nutrient content of the soil, improve the speed of nutrient flow and circulation, and continuously improve soil fertility, resulting in more new tree species in a given plot, decreased tree mortality, and allowing existing trees to obtain higher biomass (Wu et al, 2018 ; Zhu et al, 2021 ). Future studies should explore the effects of soil nutrients, light, and other environmental factors on biomass, productivity, and species community structure.…”
Section: Discussionmentioning
confidence: 99%